The Effect of Self Ability, Compensation, and Self Efficacy on Employee Performance At Rizqy Jaya Mulia Sidoarjo Company - Abellia Permatasari; Siti Mujanah (Journal of Applied Management and Business, 2021)
This purpose of this study is to analyzed the impact of Self Ability, Compensation, and Self Efficacy on Employee Performance. This study uses quantitative methods. The population and sample are 85 respondents from all employees of Rizqy Jaya Mulia company Sidoarjo. Sources of data in this research using primary data obtained directly from respondents employees by google form. Data analysis technique used in this research were Multiple Linear Regression Analysis to know the effect of Self ability, compensation and self-Efficacy on employees performance, and for proved the hypothesis used F-test and t-test. The results of analysis show that Self Ability, compensation and self-efficacy has a positive and significant effect on employee performance as partially and simultaneously. This implies that if the company wants to improve employee performance, it needs to optimize Self Ability, Compensation, and Self Efficacy by paying attention to the performance of employees and giving an award to their skills and work performance. if the company wants to improve employee performance, it is necessary to optimize Self Ability, Compensation, and Self Efficacy by paying attention to the performance of employees and providing an award for their skills and work performance.